Genomic Signatures for Individualized Treatment of Malignant Tumors - Kunz, Manfred (Current Drug Discovery Technologies, 2008)
In recent years, significant progresses have been achieved in clinical oncology due to a plethora of new chemotherapeutic drugs and agents for targeted therapy. However, clinical response and overall survival rates have not improved significantly for a large number of different tumors. This may at least in part be due to the enormous genetic heterogeneity among tumors, even within a tumor entity. Moreover, besides individual somatic mutations or combinations of these in malignant tumors, the genetic background of each individual cancer patient appears to have a major impact on treatment response and overall survival. Current DNA microarray technology allows the simultaneous gene expression analysis of all known genes, and large-scale gene expression studies have provided new molecular classifications for a series of different tumors. Evidence has also been provided that gene expression signatures of malignant tumors may predict treatment response to classical chemotherapeutic or targeted anticancer drugs. The presented report summarizes the current knowledge about the role of gene expression signatures as putative guides for treatment decisions, with the future prospect of individualized treatment approaches for cancer patients.
Keywords: Genomics